The Host Heat Shock Protein MRJ/DNAJB6 Modulates Virus Infection - Ko, Shih-Han; Huang, Li-Min; Tarn, Woan-Yuh (Frontiers in Microbiology, 2019)
A variety of pathogens take advantage of cellular heat shock proteins to complete their life cycle and exert pathogenic effects. MRJ (DNAJB6), a member of the heat shock protein 40 family, acts as a molecular chaperone for a wide range of cellular processes. MRJ mutations are linked to human diseases such as muscular dystrophy and neurodegenerative diseases. There are two MRJ isoforms generated by alternative use of terminal exons which differ in their C-terminus. This mini-review summarizes how these two MRJ isoforms participate differentially in viral production and virulence, and the possibility for MRJ as a therapeutic target.